FATAL COMPLICATION OF PEG TUBE INSERTION A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2020)
PEG stands for percutaneous endoscopic gastrostomy, a procedure in which a flexible feeding tube is placed through the abdominal wall and into the stomach. PEG allows nutrition, fluids and/or medications to be put directly into the stomach, bypassing the mouth and esophagus. PEG is currently the method of choice for medium- and long-term enteral feeding. PEG tube insertion is usually considered a safe procedure, however, complications can occur with a variable rate based on the study population. These complications can be classified as minor or major. Minor complications include wound infection, tube leakage to abdominal cavity (peritonitis), stoma leakage, inadvertent PEG removal, tube blockage, pneumoperitoneum, gastric outlet obstruction and peritonitis. While major complications are aspiration pneumonia, haemorrhage, buried bumper syndrome, perforation of bowel, necrotizing fasciitis and metastatic seeding. Bleeding from the PEG tract, gastric artery, splenic or mesenteric vein injuries (massive retroperitoneal bleeding) and rectus sheath hematoma have been reported.The incidence of major complications after PEG has been found to range from 0 to 6%.
Keywords: PEG; Percutaneous endoscopic gastrostomy; PEG tube insertion; Complications of PEG tube insertion procedure; Vascular injury to the stomach during PEG tube insertion; Haemorrhage